An 11-year analysis of peripheral nerve injuries in high school sports - Zuckerman, S. L.; Kerr, Z. Y.; Pierpoint, L.; Kirby, P.; Than, K. D.; Wilson, T. J. (The Physician and Sportsmedicine, 2019)
Introduction: Sports surveillance databases provide valuable information regarding common ailments, yet fewer studies have focused on more rare peripheral nerve injuries. Our objective was to characterize peripheral nerve injuries in high school athletics with respect to incidence, time loss, mechanism, and diagnoses.